2009
DOI: 10.3155/1047-3289.59.7.857
|View full text |Cite
|
Sign up to set email alerts
|

Real-World Energy Use and Emission Rates for Idling Long-Haul Trucks and Selected Idle Reduction Technologies

Abstract: Long-haul freight trucks typically idle for 2000 or more hours per year, motivating interest in reducing idle fuel use and emissions using auxiliary power units (APUs) and shore-power (SP). Fuel-use rates are estimated based on electronic control unit (ECU) data for truck engines and measurements for APU engines. Engine emission factors were measured using a portable emission measurement system. Indirect emissions from SP were based on average utility grid emission factors. Base engine fuel use and APU and SP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 2 publications
1
10
0
Order By: Relevance
“…Individually, by 2050, emissions of CH 4 reach up to 578886.17 metric tons, BC emissions reach 410376.38 metric tons and CO 2 emissions up to 1498164.01 metric tons. A comparison between these results and known atmospheric projected values, showed that these models probed a well representation of global pollution budget previously reported (Haro et al, 2019;Vitolo, Scutari, Ghalaieny, Tucker & Russell, 2018;Fuglestvedt et al, 2010;Frey & Kuo, 2009). 2 2 5 6 -1 5 3 6 • 2 8 7 • Stockwell, C., Yokelson, R., Kreidenweis, S.,…”
Section: Yearsupporting
confidence: 68%
“…Individually, by 2050, emissions of CH 4 reach up to 578886.17 metric tons, BC emissions reach 410376.38 metric tons and CO 2 emissions up to 1498164.01 metric tons. A comparison between these results and known atmospheric projected values, showed that these models probed a well representation of global pollution budget previously reported (Haro et al, 2019;Vitolo, Scutari, Ghalaieny, Tucker & Russell, 2018;Fuglestvedt et al, 2010;Frey & Kuo, 2009). 2 2 5 6 -1 5 3 6 • 2 8 7 • Stockwell, C., Yokelson, R., Kreidenweis, S.,…”
Section: Yearsupporting
confidence: 68%
“…Flaws in the accountability measures were revealed by real-world emission testing (e.g., source-dominated studies using in-plume and cross-plume measurements in source-dominated environments such as roadsides, parking garages, tunnels, etc.). [117][118][119][120][121][122][123][124][125][126][127] An example of AQM for multipollutants and multiple effects is the long-term regional strategy for health, visibility, and ecological benefits in the U.S. Midwest, U.S. Northeast, and Canadian southeast regions. The O 3 Transport Assessment Group (OTAG), 128 NO x SIP call, [129][130][131][132][133]51,134,135 and its failure to reduce emissions from grandfathered power generators, the Regional Haze Rule, 10,47,94,136 and the CAIR and Clean Air Mercury Rules 12,134,137-142 all address multipollutants and in some cases required continuous emission monitors (CEMs) for accountability.…”
Section: Invited Comments By Dr John Watsonmentioning
confidence: 99%
“…In the present case the following hypotheses were made: all the idling vehicles are heavy-duty diesel vehicles (HDDV); all of them are standing with an auxiliary power unit (APU) in use; all the vehicles are always idling for the whole period of breaking in the parking lot, no matter the season of the year nor the hour of the day. The emission rate of each idling vehicle was determined according to standard values for this type of engine idling with the APU in use [7,10]: given the annual mean number of parked trucks, known from the available traffic data, the annual mean emission of the parking lot was easily calculated and modulated with data-based seasonal and hourly patterns. Table 5 summarises the emission rates of the three sources representing the parking.…”
Section: Parking Lotmentioning
confidence: 99%